Geomorphologische Spezialkarte des Rheinhessischen Tafel- und Hügellandes (Südteil) - Leser, Hartmut (ERDKUNDE, 1967)
Within the framework of a quaternary geomorphic study in the plateau and hill area of Rheinhessen, a special geomorphic map on 1 : 50 000 scale was drawn up (Sheet L 6314 Alzey). The map has a morphographic and morphogenetic character and in spite of its detailed con tent attempts to give a general picture. In order to attain this goal, the key is presented once in spatial-genetic units limestone plateaus, Riedel units etc.) and another time through suitable means of presentation (colours, isohypsic underlay, slope-angle scanner) and, despite the complexity of content, this gives the map an appearance of plasticity. The operating motive behind the detailed geomorphic map is a wish for general survey and detail. Observations on the content are preceded by reflections on the development of the special geomorphic map, which at the same time should present a collection of selected references to literature on the topic. Attention is drawn especially to the central significance of the geomorphic maps, both base-maps and detailed maps, of Kugler, which are recognized as the most comprehensive cartographic presentation of geomorphic data.